Guidelines for the Development of Adjustment Services in Rehabilitation - Baker, Richard J.; Sawyer, Horace W.; Alabama State Vocational Rehabilitation Service, Montgomery (Washington, D.C. : Distributed by ERIC Clearinghouse, 1971)
The State guide provides rehabilitation personnel with guidelines for structuring and implementing adjustment programs to prepare clients to become more adequately functioning community members. Part 1 discusses objectives, general techniques, and learning/motivation principles. Appropriate techniques include: individual counseling, group counseling, work experience setting, behavior modification, attitude therapy, and individual and classroom instruction. Part 2 familiarizes the reader with behavior analysis terminology and procedures. In Part 3 a rehabilitation educator/administrator discusses the relationship of vocational evaluation and adjustment services. This section also considers behavior descriptions, attitude analysis, work habit patterns, and adjustment skills assessment. Focusing on program development, Part 4 covers: (1) planning stages (need, space, financial aspects, time, and staff); (2) innovation/implementation (objectives, client supervision/reporting, and curriculum outlines/lesson plans); and (3) resource materials. Part 5 provides examples of training area outlines and lesson plans dealing with: job readiness, personal appearance and hygiene, budgeting, and social/work/recreational adjustment. A content outline of information areas and a survival word list necessary to daily living adjustment also are included. The concluding section discusses client followup (sample letters to clients and employers and employee performance forms included). The appendix consists of 188 references coordinately indexed to 15 subject categories. (EA)
Availability: Alabama Rehabilitation Media Service, 216 Petrie Hall, Auburn University, Auburn, Alabama 36830 ($2.50).
Microfiche.
Keywords: Adjustment Counselors; Adjustment (to Environment); Daily Living Skills; Educational Objectives; Guidelines; Learning Motivation; Lesson Plans; Rehabilitation Counseling; Rehabilitation Programs; Resource Materials; Vocational Adjustment; Vocational Followup; Guides, General